A business plan for Wheat State Distilling - Bahre, David (Kansas State University, 2014)
This thesis was written as a business plan for the purpose of securing funds for a new micro distillery. Wheat State Distilling is an artisan distillery, manufacturing and selling premium hand-crafted spirits from the regions finest ingredients. I plan to distill premium vodka, whisky, bourbon, rum, gin and liqueurs as well as a luxury line of reserve products. Kansas established a micro-distillery license in July 2012 that opens up the market to this new type of business. The micro-distillery trend is growing across the U.S. and I plan to establish myself as a key player in the region. I will be entering the market early in the industry’s life cycle when consumer interest and demand are high. The proposed location in Wichita Kansas takes advantage of the largest city in Kansas with a metro area population of 630,721 in 2011. The location has visible signage from Interstate 135. The distillery will offer tours and a tasting room. We are able to give customers free samples and sell cocktails to induce purchase. We will use direct sales as well as restaurant and liquor store sales thru distributors. I will be marketing my premium products to upper-middle class and wealthy consumers. My extensive product line will allow marketing to a wide age range and to both sexes. We will focus on online and social media as well as distributor incentives and in-store promotions. Participation in local and regional events for sampling and advertising will increases brand awareness. Analysis of monthly production levels of each of the proposed product has been completed to maximize profits considering time and equipment constraints, cost of inputs and sale price. Regression analysis has been completed examining many factors that contribute to the selling price of micro distilled spirits. Financial models for years one through ten with risk analysis are included. If I reach my sales goals of 25,000 cases per year by year five, which is equal to my closest competition, High Plains Distilling, there is a potential for $548,500 or more per year in profit. I am seeking a loan for $300,000.
Keywords: Distilling; Alcohol; Business plan; Ag tourism